Development and Application of Biopesticides for the Management of Disease Vectors and Pests of Public Health Importance - Tawatsin, Apiwat; Thavara, Usavadee (British Journal of Healthcare and Medical Research, 2023)
The development and practical use of natural products occurred in the late 1970s when a spore-forming bacterium producing enterotoxins was discovered. This organism was designated as Bacillus thuringiensis ssp. israelensis (Bti). By 1985, large quantities of Bti formulations were employed in mosquito and black fly control programs globally. As research efforts in this area continued, a second bacterium Bacillus sphaericus (Bsph) was isolated and found to be highly effective against most mosquito species. This entomopathogen found its way into mosquito control around 1997. Today, both these (Bti and Bsph) microbial control agents are produced by large-scale fermentation processes in many countries. Recent advances in formulation technology of both bacteria have increased their usefulness in vector control programs. Another soil bacterium known as Saccharopolyspora spinosa (Actinomycetes), was discovered, producing bioactive components known as spinosyn A and spinosyn D. Large-scale fermentation technology has been developed and the product known as spinosad was produced and developed in agriculture, and recently for use in public health. However, spinosad has not been used to any great extent in public health as yet. All three microbial control agents have a good margin of safety for mammals, birds, and wildlife and are environmentally friendly. Considerable efforts were directed toward developing plant extracts for vector control, especially mosquitoes. In this context, plant-based extracts were formulated for the control of larval and adult mosquitoes. Some of the plant parts were used in manufacturing mosquito coils which number into the billions on a worldwide basis; however, only a small proportion of coils are manufactured with plant-derived products. A major area for the development of plant-based products is the use of plant essential oils which are formulated in various ways for personal protection from the attack of hematophagous insects. A number of such insect-repellent products are commercialized in many countries. The public has the perception that plant-based and other natural products are environmentally friendly and safer to use for vector control or apply to human skin as personal protectants than synthetic chemicals. In this paper, we will dwell upon the research and development efforts leading to the development, production, and application of microbial control agents, and phytochemicals for the control of adult and preimaginal stages of disease vectors, as well as the development and use of plant essential oils for personal protection from anthropophilic insects.